3D Models Reveal the Influence of Achilles Subtendon Twist on Strain and Energy Storage - Knaus, Katherine R.; Blemker, Silvia S. (Frontiers in Bioengineering and Biotechnology, 2021)
The Achilles tendon (AT) has complex function in walking, exchanging energy due to loading by the triceps surae muscles. AT structure comprises three subtendons which exhibit variable twist among themselves and between individuals. Our goal was to create 3D finite element (FE) models to explore AT structure-function relationships; by simulating subtendon loading in FE models with different amounts of twist, we investigated how variation impacts fascicle lengths, strains, and energy storage. Three tendon FE models, built with elliptical cross sections based on average cadaver measurements, were divided into subtendons with varied twist (low, medium, high) and equal proportions. Tendon was modeled as transversely isotropic with fascicle directions defined using Laplacian flow simulations, producing fascicle twist. Prescribed forces, representing AT loading during walking, were applied to proximal subtendon ends, with distal ends fixed, and tuned to produce equal tendon elongation in each case, consistent with ultrasound measurements. Subtendon fascicle lengths were greater than free tendon lengths in all models by 1-3.2 mm, and were longer with greater subtendon twist with differences of 1.2-1.9 mm from low to high twist. Subtendon along-fiber strains were lower with greater twist with differences of 1.4-2.6%, and all were less than free tendon longitudinal strain by 2-5.5%. Energy stored in the AT was also lower with greater twist with differences of 1.8-2.4 J. With greater subtendon twist, similar elongation of the AT results in lower tissue strains and forces, so that longitudinal stiffness of the AT is effectively decreased, demonstrating how tendon structure influences mechanical behavior.